ANALISIS PENCEGAHAN BULLYING PADA SEKOLAH DASAR DI SDN MODEL TERPADU MADANI - Juniantari, Ni Putu Eka; Anta, I Made Nuhari; Kertayasa, I Ketut (STAH Dharma Sentana Sulawesi Tengah, 2024)
The research aims to determine prevention efforts and the implications of efforts to prevent bullying in elementary schools at SDN Model Terpadu Madani. The method used in the research is a qualitative descriptive method. Data collection techniques by means of observation, interviews and documentation. Determining informants using snowball sampling The principal is the key informant. The data analysis techniques in this research are data collection, data reduction, data presentation and drawing conclusions. The results of the research are prevention of bullying carried out by the Principal and class teachers by instilling good character values, conducting outreach about bullying, taking approaches and providing motivation, creating a safe and comfortable school environment. The prevention is carried out by parents of students by teaching children positive things, instilling character values ​​and religious values. The Head of Elementary School Development prevents school bullying by forming a violence prevention and handling team that carries out outreach about bullying. The implication that occurs after carrying out prevention is that students understand and understand the meaning of bullying, the impact of bullying and the forms of bullying. Students have good character, are open to teachers and parents. Preventing bullying carried out by the school can result in minimal cases of bullying occurring at the Madani Integrated Model Elementary School so that it can be used as an example by other schools.